An Effort to Determine Blood Group and Gender from Pattern of Finger Prints - Raloti, Sandip K; Shah, Kalpesh A; Patel, Viras C; Menat, Anand K; Mori, Rakesh N; Chaudhari, Nishith K (National Journal of Community Medicine, 2013)
Introduction: Two person having identical fingerprints is about one in 64 thousand millions. A reliable personal identification is critical in the subject of forensics as is faced with many situations like civil, criminal, commercial and latest in financial transaction frauds, where the question of identification becomes a matter of paramount importance. In this study we have made an effort to “study a relationship between pattern of fingerprint, gender and blood group”. Materials and methods: This study was carried out in 2012 on 89 medical students (62 male & 27 female), randomly chosen belonging to the age group 17- 21 at B. J. Medical College, Ahmedabad Gujarat, India. The finger-prints were taken of all ten fingers over unglazed white paper using printer’s ink. Pattern of fingerprints were observed by powerful hand lens and recorded. Note was made of the sex, age, ABO blood groups. Results: Results show that whorls occur more frequently in males, whereas, loops occur more frequently in females. Loops are predominant in blood group B+ and whorls are predominant in blood group O+ (p < 0.05). We see an association between fingerprint patterns, blood group and gender. Conclusion: From our study we may conclude that there is an association between distribution of fingerprint patterns, blood group and gender and thus in our opinion, prediction of gender and blood group of a person is possible based on his/her fingerprint patterns.